2022
DOI: 10.1002/ep.13850
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis on engine operating in dual fuel mode with different energy fractions of sustainable HHO gas

Abstract: Carbon emission and problems associated with the world have been the major concerns for the past few decades. The world governments have implemented stringent emission norms to reduce the pollution created by hydrocarbon combustion in automobiles. The use of gaseous fuels in IC engines has gained interest among the research community. In the present research work, hydrogen, and oxygen (HHO gas) are produced together in an electrolyzer unit and is fed into the engine intake manifold before the carburetor. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…The BSFC decreases with an increase in load intensity and CR; however, it initially decreases and later increases with fuel mode changes from SF1 to DF. Similar results have been observed for the fuel mode type in refs ( 46 ) and ( 47 ). Increasing the load and CR ensures better combustion with increasing cylinder pressure and temperature in the combustion chamber, thereby reducing BSFC in the test engine.…”
Section: Resultssupporting
confidence: 88%
“…The BSFC decreases with an increase in load intensity and CR; however, it initially decreases and later increases with fuel mode changes from SF1 to DF. Similar results have been observed for the fuel mode type in refs ( 46 ) and ( 47 ). Increasing the load and CR ensures better combustion with increasing cylinder pressure and temperature in the combustion chamber, thereby reducing BSFC in the test engine.…”
Section: Resultssupporting
confidence: 88%
“…Several research works evaluated the influence of a mass proportion of methanol/diesel mixtures. The HRR rose as the diffusive combustion duration was reduced based on the experimental outcomes. …”
Section: Introductionmentioning
confidence: 99%
“…Sahin et al analyzed the influence of the butanol effect in a diesel engine. The study showed that changing the proportion of butanol and engine working environments affected engine efficiency, SFC, and pollutants. , Imdadul et al showed that adding butanol to diesel enhanced the cylinder pressure (CP) and burning rate. HC emissions increased, but soot emissions dropped in terms of emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The current study is the first one which studies it utilizing an enhanced technology, hydrodynamic cavitation, which can produce biodiesel that is both cheaper and cleaner. 40,41 There has not been much research done on using UV light and hydrodynamic cavitation to produce biodiesel, 42−45 thus there are opportunities to experiment in this field. 46 The present study is intended to investigate the suitability of TME as a potential blending element for use in CI engines.…”
Section: Introductionmentioning
confidence: 99%